VIDEO PROFILE JURUSAN SISTEM KOMPUTER JENJANG STRATA SATU PADA STMIK RAHARJA TANGERANG - Adi Kusuma Widya Tama; Azwar Aditya Putra; Muhamad Azis Fikri (UNIVERSITAS RAHARJA, 2018)
Currently, many formal and non formal education institutions are competing to get new students, so the profile of an educational institution becomes an important identity in introducing the institution to the general public. Various ways are used to socialize his profile, one of them STMIK Raharja Tangerang. In this modern era, multimedia plays an important role in the field of marketing as a promotion. The purpose of this study is, for prospective students / i new interested in the Department of Computer Systems, as well as a means of information and promotion effective and attractive to the general public. The problem is, the previous SK's promotional program only uses the brochure and banners media which information is not complete and interesting, for that SK Department requires video profile media capable of providing detailed information and interesting about the Department of Computer Systems, The research methods are: problem analysis, data, media design analysis and, media production concept (KPM). The results of his research in the form of video video profile Department of Computer Systems, which explains the profile of Computer Systems Department STMIK Raharja include CCIT and Computer System concentration, learning methods, excellence, and facilities. With the design of video media profile majors Computer Systems STMIK Raharja can be an attraction to increase interest in prospective new students in the Department, and become an informative and useful media for the general public.